Orbital Integrals on Reductive Lie Groups and Their Algebras - Bulnes, Francisco (IntechOpen, 2013)
The purpose is to present a complete course on global analysis topics and establish some orbital applications of the integration on topological groups and their algebras to harmonic analysis and induced representations in representation theory.